The representation of women in selected isiXhosa drama books - Klaas, Sibusiso (Rhodes University, Faculty of Humanities, School of Language & Literatures: African Language Studies Section)
The current study focused on the representation of women in isiXhosa drama books. The aim of the study was to understand how women are represented in these post-1990 dramas written by both female and male authors. Furthermore, the study aimed to look at whether the authors took note of developments made by African women in a broader context such as social, political, spiritual and economic spheres. The study followed a pragmatic approach which is useful to analyse drama, the meanings and the events related to situations. A discourse analysis was also applied as it is difficult to separate it from pragmatics. This means that the study outlined the correlation of pragmatics with discourse analysis and drama. Four isiXhosa books were selected which are Iinkunzi ezimbini by Hlumela Mothlabane 1994, Yeha mfazi obulala indoda 1997 and Kuphek'amadoda kupheth'abafazi We-ena! 2007 by Lubabalo Livingstone Ngewu and Imida by Nompumezo Buzani 2016. Episodes from the four selected isiXhosa drama books were identified. Upon identifying the episodes, they were categorised in to themes in order to highlight the representation of women in the books. This was done using a qualitative research method because it useful to be used in natural setting to understand meanings and social life. Many themes were identified in the four selected isiXhosa drama books. The dominating themes are women who are educated, employed and do not tolerate ill treatment. This shows that the authors in a way are paying attention to the events occurring post-1990 as some of these were not popular pre-1990. The study acknowledges that there is limited research conducted that analyses drama books from both male and female authors. Therefore, future studies could look into this.
Keywords: Women in literature; Xhosa drama -- 20th century -- History and criticism; Xhosa drama -- 21st century -- History and criticism; Pragmatics; Discourse analysis; Mothlabane, H. E. (Hlumela Elephylet), 1953- -- Criticism and interpretation; Ngewu, L. L. (Lubabalo Livingstone), 1950-2012 -- Criticism and interpretation; Buzani, Nompumezo -- Criticism and interpretation